The Cyclical Behavior of Equilibrium Unemployment and Vacancies Across OECD Countries - Pedro S. Amaral; Murat Tasci (Koç University-TÜSİAD Economic Research Forum (ERF), 2014)
We show that the inability of a standardly-calibrated labor search-and-matching model to account for labor market volatility extends beyond the U.S. to a set of OECD countries. That is, the volatility puzzle is ubiquitous. We argue cross-country data is helpful in scrutinizing between potential solutions to this puzzle. To illustrate this, we show that the solution proposed in Hagedorn and Manovskii (2008) continues to deliver counterfactually low volatility in countries where labor productivity persistence and/or steady-state job-finding rates are sufficiently low. Moreover, the model's ability to generate high enough volatility depends on vacancy-filling rate levels that seem counterfactual outside the U.S.
Keywords: E24; E32; J63; J64; 330; Labor Market; Vacancies; Unemployment; OECD countries